Ongoing mumps outbreak among adolescents and young adults, Ireland, August 2018 to January 2020 - Ferenczi, Annamaria (Euro Surveill, 2020)
Between 18 August 2018 and 24 January 2020, 3,736 mumps cases were notified in Ireland. The highest numbers of notifications were observed in the age group 15–24 years. Vaccination status was reported for 32% (n = 1,199) of cases: 72% of these had received two doses of measles-mumps-rubella (MMR) vaccine. Vaccination uptake after free MMR vaccination targeting colleges and universities since early 2019 was low. Therefore, a national media campaign began in January 2020.